Now [compact disc] - Nash, Graham, 1942-; Nash, Graham, 1942- (BMG Rights Management, 2023)
Nash's tenor is among rock's most recognizable, and as resonant as his voice of conscience as a songwriter. He started The Hollies with his childhood friend Allan Clarke in 1961, before embarking on a lifelong musical journey, solo and with David Crosby, Stephen Stills and Neil Young.